The contribution of Letseng Diamonds Mine Corporate Social Responsibility in the Mokhotlong district - Hlojeng, Tsepo (University of the Free State, 2020)
Abstract not available
Dissertation (MDS (Development Studies))--University of the Free State, 2020
Keywords: Community involvement - mining companies; Corporate social responsibility; Letseng Diamonds - Lesotho